Misanthropy of Form: John Banville’s Henry James - Toal, Catherine (ABEI Journal, 2021)
Mrs Osmond (2017) is unique to date among John Banville’s non-pseudonymous novels in having a female protagonist and no first-person voice. Reviewers have hailed it as a pastiche faithful to the style and dramatic situation of the classic work for which it offers a sequel, Henry James’s The Portrait of a Lady (1881). This essay argues that Mrs Osmond dismantles all the central elements of Portrait. Its manner of doing so shows the fundamental importance of a quality often observed in Banville’s male narrators—misanthropy—to the design of his novels, particularly its close connection to the aspect of his work most highlighted by scholars: metafictional self-reflexivity.